Interplay Role of Heat-Moisture Treatment and Lipid from Egg yolk and Margarine on Functional and Pasting Properties of Banana Flour - Yana Cahyana; Tomi Nugraha; Nabila Aprilira; Karina Ayuningtias; Giffary Pramafisi Soeherman; Herlina Marta; Tensiska Tensiska (Polish Journal of Food and Nutrition Sciences)
Egg yolk and margarine are commonly applied in starchy food processing as a lipid source. Both may affect the starch properties to different extent. Therefore, the effects of adding egg yolk (0.3, 1.0, and 1.7 g/100 g of flour) and margarine (1, 3, and 5 g/100 g of flour) to banana flour on the complex formation of gelatinized starch–lipid and on paste functional properties were investigated in this study. Native banana flour was used as a control. The complexing index (CI) value increased with the increasing egg yolk or margarine content in the paste. Egg yolk lipids formed complexes with flour starch more favorably than margarine lipids. The heat-moisture treatment (HMT) of banana flour increased its ability to form a complex. Complex formation may partly affect the swelling volume (SV) and freeze-thaw stability (FTS) of pastes. The decrease in SV was smaller in the paste with egg yolk than with margarine. Egg yolk also led to a lesser syneresis and solubility than margarine. For freeze-thaw stability, the interplay roles between the reducing effect of lipid addition and the increasing effect of HMT led to an increased syneresis suggesting that HMT factor prevailed. The reducing effect of lipid addition on egg yolk complex solubility predominated the increasing impact of HMT. Lipid source did not affect pasting properties except set back viscosity. HMT-pretreatment played a major role in the alteration of pasting properties compared to the lipid content.